2019
DOI: 10.1371/journal.pmed.1002771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeat prenatal corticosteroids given to women at risk of preterm birth: An individual participant data meta-analysis

Abstract: Background Infants born preterm compared with infants born at term are at an increased risk of dying and of serious morbidities in early life, and those who survive have higher rates of neurological impairments. It remains unclear whether exposure to repeat courses of prenatal corticosteroids can reduce these risks. This individual participant data (IPD) meta-analysis (MA) assessed whether repeat prenatal corticosteroid treatment given to women at ongoing risk of preterm birth in order to benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 38 publications
2
52
1
12
Order By: Relevance
“…This issue is particularly relevant due to the common practice of multiple administrations of glucocorticoids to pregnant women during late gestation to ensure the survival of the preterm newborns. Even though synthetic glucocorticoids, such as dexamethasone (DEX) or betamethasone, have been extensively used rather than cortisol or hydrocortisone (Jobe, 2003;Oliveira et al, 2006;Singh et al, 2012), the natural glucocorticoid is increasingly considered as an alternative therapy during pregnancy (Crowther et al, 2019). Therefore, a long-term follow-up in children who were treated in utero with glucocorticoids is strongly recommended.…”
Section: Resultsmentioning
confidence: 99%
“…This issue is particularly relevant due to the common practice of multiple administrations of glucocorticoids to pregnant women during late gestation to ensure the survival of the preterm newborns. Even though synthetic glucocorticoids, such as dexamethasone (DEX) or betamethasone, have been extensively used rather than cortisol or hydrocortisone (Jobe, 2003;Oliveira et al, 2006;Singh et al, 2012), the natural glucocorticoid is increasingly considered as an alternative therapy during pregnancy (Crowther et al, 2019). Therefore, a long-term follow-up in children who were treated in utero with glucocorticoids is strongly recommended.…”
Section: Resultsmentioning
confidence: 99%
“…For IgE-mediated reactions skin prick tests or intradermal tests are used for confirming the diagnosis, but for serum sickness-like reactions there are no available tests. Considering our patient was pregnant we did not perform a drug provocation test (7).…”
Section: Discussionmentioning
confidence: 99%
“…We used low doses of systemic corticosteroids as premedication in order to induce tolerance. The reason for using a low dose corticosteroid was the pregnancy (7).…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane review which included 4733 women and 5700 babies from 10 trials showed a significant improvement in respiratory distress syndrome (RR: 0.83, 95% CI: 0.75‐0.91) and serious infant outcome (RR: 0.84, 95% CI: 0.75‐0.94) but a significant decrease in mean birth weight which was no longer significant when adjusted for gestational age . A recent individual participant meta‐analysis which included 11 randomized trials involving 4857 women and 5915 infants reported a significant decrease in the use of respiratory support (RR: 0.91, 95% CI: 0.85‐0.97) but also a significant decrease in birthweight in the group exposed to repeat prenatal steroids (mean difference: −0.12, 95% CI: −0.18 to −0.06) . No differences were seen in composite serious outcome for child or woman …”
Section: Controversies In the Preterm Periodmentioning
confidence: 99%
“…A recent individual participant meta‐analysis which included 11 randomized trials involving 4857 women and 5915 infants reported a significant decrease in the use of respiratory support (RR: 0.91, 95% CI: 0.85‐0.97) but also a significant decrease in birthweight in the group exposed to repeat prenatal steroids (mean difference: −0.12, 95% CI: −0.18 to −0.06) . No differences were seen in composite serious outcome for child or woman …”
Section: Controversies In the Preterm Periodmentioning
confidence: 99%